Tinea Corporis Et Cruris - Refi Syifa Ghinanda; Mohd Mimbar Topik (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Dermatophytes themselves are filamentous fungi with the ability to attack keratinized tissue such as skin, hair and nails. Classically, dermatophytes are divided into three genera, namely Trichophyton, Epidermophyton, and Microsporum. Dermatophyte infections are generally limited to the stratum corneum of the epidermis, especially in tropical areas with hot conditions that are ideal for the growth of dermatophytes, especially in moist areas of the body. National epidemiological data on tinea corporis for Indonesia is still not available. According to data on dermatophytosis cases found in the Skin and Venereology Mycology Division of Dr. Soetomo Surabaya for the 2014-2016 period, it was found that the percentage of tinea corporis cases was 56.1%, followed by tinea cruris at 34.3%, and tinea capitis at 6.4%. Predisposing factors for this disease in the host include lack of hygiene and immunocompromised conditions. Fold areas including the groin and armpits are more susceptible to infection due to excessive sweating and friction. Environmental factors that put a person at a higher chance of contracting the disease include high humidity, high temperatures and tight clothing. The clinical manifestation is the presence of a characteristic circular lesion, usually with firm borders, pink to erythematous with raised edges. As the lesion develops, the central area of ​​the lesion is usually calmer (central healing) and the lesion is annular with a scaly edge area. Supporting examinations were carried out with KOH solution. Management in general is in the form of educating patients to wear light and loose clothing and keep the skin clean and dry. Specific management includes administering topical antifungals or systemic antifungals